Improving Tax Administration in Developing Countries. (Washington, D.C. : International Monetary Fund, 1992)
Taxation, like politics, is the art of the possible--yet most public finance texts ignore the critical role played by tax administration in restoring macroeconomic balance and promoting equity and efficiency. This volume, edited by Richard M. Bird and Milka Casanegra de Jantscher, fills a gap in the literature by linking tax policy and tax administration reform and exploring ways to improve taxpayer compliance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet